2021
DOI: 10.3390/cells10082102
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vectors Delivered with Biomaterials as Therapeutics for Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a devastating trauma that can cause permanent disability, life-long chronic issues for sufferers and is a big socioeconomic burden. Regenerative medicine aims to overcome injury caused deficits and restore function after SCI through gene therapy and tissue engineering approaches. SCI has a multifaceted pathophysiology. Due to this, producing therapies that target multiple different cellular and molecular mechanisms might prove to be a superior approach in attempts at regeneration. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Additionally, safety concerns, such as immune response activation and carcinogenic risk, are simultaneously associated with the injection of many viruses. [2] The com-bination of biomaterials and lentiviruses may represent a strategy for SCI treatment. [35] Our previous research showed that a PDAmodified PLLA electrospun fiber had good hydrophilicity and maintained the biological activity of the grafted antibody.…”
Section: Biological Characterization Of the Functional Electrospun Fi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, safety concerns, such as immune response activation and carcinogenic risk, are simultaneously associated with the injection of many viruses. [2] The com-bination of biomaterials and lentiviruses may represent a strategy for SCI treatment. [35] Our previous research showed that a PDAmodified PLLA electrospun fiber had good hydrophilicity and maintained the biological activity of the grafted antibody.…”
Section: Biological Characterization Of the Functional Electrospun Fi...mentioning
confidence: 99%
“…Current methods of combining viral vectors with biomaterials include covalent and noncovalent approaches, such as surface modification/functionalization of biomaterial, encapsulation of lentiviral vectors (LVs) within hydrogels, and modification of the LV envelope. [ 2 ] Their advantage is the slow release of viral vectors, increasing the local concentration of the virus, increasing the transfection efficiency, and minimizing potential off‐target effects. So, virus‐engineered biomaterials have become hot research to promote tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the critical role of biomaterial scaffolds in forming a beneficial regeneration microenvironment for repairing injured spinal cord tissues, they have been used as supporting and carrier platforms for stem cells. The combined use of stem cells and scaffolds could facilitate the reconstruction of the microenvironment at the injury site [50]. Moreover, immobilizing cells into scaffolds could control the diffusion rate after implantation [15].…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…[3][4][5][6] In patients with SCIs, the main injury locations include the thoracic, lumbosacral, and cervical regions. [7,8] Corresponding strengthening function interventions are needed for injuries at different locations. In recent years, studies have confirmed that rehabilitation training interventions can effectively reduce secondary injury, restore spinal cord function, reduce the incidence of complications, and restore normal spinal cord function to the greatest extent.…”
Section: Introductionmentioning
confidence: 99%